Body Mass Index in Mild Cognitive Impairment According to Age, Sex, Cognitive Intervention, and Hypertension and Risk of Progression to Alzheimer's Disease - Joo, Soo Hyun; Yun, Se Hee; Kang, Dong Woo; Hahn, Chang Tae; Lim, Hyun Kook; Lee, Chang Uk (Frontiers in Psychiatry, 2018)
Introduction Mild cognitive impairment (MCI) is a prodromal stage of dementia. The association of body mass index (BMI) and progression to Alzheimer’s disease (AD) in MCI subjects according to age, sex, and cognitive intervention remains unknown. We investigated the relationship between BMI and the risk of progression to AD in subjects with MCI, as well as the effect of BMI on progression to AD depending on age, sex, cognitive intervention, and chronic diseases. Methods Three hundred and eighty-eight MCI subjects were followed for 36.3±18.4 months, prospectively. They underwent neuropsychological testing more than twice during the follow –up period. The MCI subjects were categorized into underweight, normal weight, overweight, and obese subgroups. The associations between baseline BMI and progression to AD over the follow-up period were estimated using Cox proportional hazard regression models. Data were analyzed after stratification by age, sex, cognitive intervention, and chronic diseases. Results After adjustment for the covariates, the underweight MCI group had a higher risk of progression to AD (hazard ratio [HR]: 2.38, 95% confidence interval [CI]: 1.17-4.82) relative to the normal weight group. After stratifying by age, sex, cognitive intervention, and chronic diseases, this effect remained significant among females (HR: 3.15, 95% CI: 1.40-7.10), the older elderly ≥75 years old (HR: 3.52, 95% CI: 1.42-8.72), the non-intervention group (HR: 3.06, 95%CI: 1.18-7.91), and the hypertensive group (HR: 4.71, 95% CI: 1.17-18.99). Conclusion These data indicate that underweight could be a useful marker for identifying individuals at increased risk for AD in MCI subjects. This association is even stronger in females, older elderly subjects, the non-cognitive intervention group, and the hypertensive group.